Llama llama. Best summer ever! [videorecording (DVD)] - Dewdney, Anna (Llama Llama., 2019)
These heartwarming tales are based on the award-winning book series by author and illustrator Anna Dewdney. Join the adventurous young llama, Nelly Gnu, Luna Giraffe, Euclid the Sheep, and Gilroy Goat as they explore their safe, friendly hometown and make childhood memories. On this DVD, come alongside him as he camps, boats, floats, and swims his way through his best summer ever! Adventure and learning await with the little llama and his pals!